Evaluation of the Relationship between Explosive Power and Anthropometric and Body Composition Indices in Female Volleyball Players - Mehdi Kushkestani; Shiva Ebrahimpour Nosrani; Mohsen Parvani; Sohrab Rezaei; Negin Karimi Nazar (Allameh Tabataba'i University Press, 2019)
Background: Volleyball is known as sport that requires high physical fitness, including muscle power, agility and reaction; hence, body composition and anthropometric features play important roles in this field. The purpose of this study was to investigate the relationship between anthropometric and body composition indices with lower limb explosive power in female volleyball players. Material and method: This correlational study was conducted in which 16 semi-professional female volleyball players with an average age of 20.4 ± 1.34 years and BMI of 22.09 ± 3.42 kg/m2 voluntarily participated. All volleyball players had a history of participation in the Tehran province volleyball league. First, data were collected and recorded by demographic questionnaire. Then, the body composition (fat percentage, muscle mass, visceral fat) was measured and recorded in the 3-hours fasting condition by body analysis device (OMRUN Bf511). Finally, Sargent Vertical Jump Test was used to evaluate explosive power of the lower limb muscles. Results: Pearson correlation coefficient was used at the significant level p Conclusion: The results of this study show that resistance training along with volleyball specific power training can increase the muscle mass as well as it is at the same time.